Discover a world of knowledge at Westonci.ca, where experts and enthusiasts come together to answer your questions. Experience the ease of finding reliable answers to your questions from a vast community of knowledgeable experts. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
Let's take each pair of polynomials one by one and find their sums step-by-step.
### 1. Adding \(12x^2 + 3x + 6\) and \(-7x^2 - 4x - 2\)
#### Step-by-Step Addition:
- Combine the coefficients of \(x^2\):
\(12x^2 + (-7x^2) = (12 - 7)x^2 = 5x^2\)
- Combine the coefficients of \(x\):
\(3x + (-4x) = (3 - 4)x = -x\)
- Combine the constants:
\(6 + (-2) = 6 - 2 = 4\)
Thus, the sum of the first pair of polynomials is:
[tex]\[5x^2 - x + 4\][/tex]
### 2. Adding \(2x^2 - x\) and \(-x - 2x^2 - 2\)
#### Step-by-Step Addition:
- Combine the coefficients of \(x^2\):
\(2x^2 + (-2x^2) = (2 - 2)x^2 = 0\)
- Combine the coefficients of \(x\):
\(-x + (-x) = (-1 - 1)x = -2x\)
- Combine the constants:
[tex]\[0 - 2 = -2\][/tex]
Thus, the sum of the second pair of polynomials is:
[tex]\[-2x - 2\][/tex]
### 3. Adding \(x^3 + x^2 + 2\) and \(x^2 - 2 - x^3\)
#### Step-by-Step Addition:
- Combine the coefficients of \(x^3\):
\(x^3 + (-x^3) = (1 - 1)x^3 = 0\)
- Combine the coefficients of \(x^2\):
\(x^2 + x^2 = (1 + 1)x^2 = 2x^2\)
- Combine the constants:
\(2 + (-2) = 2 - 2 = 0\)
Thus, the sum of the third pair of polynomials is:
[tex]\[2x^2\][/tex]
### 4. Adding \(x^2 + x\) and \(x^2 + 8x - 2\)
#### Step-by-Step Addition:
- Combine the coefficients of \(x^2\):
\(x^2 + x^2 = (1 + 1)x^2 = 2x^2\)
- Combine the coefficients of \(x\):
\(x + 8x = (1 + 8)x = 9x\)
- Combine the constants:
\(0 + (-2) = -2\)
Thus, the sum of the fourth pair of polynomials is:
[tex]\[2x^2 + 9x - 2\][/tex]
### Final Results:
We have found the sums of the pairs of polynomials as follows:
1. \(5x^2 - x + 4\)
2. \(-2x - 2\)
3. \(2x^2\)
4. [tex]\(2x^2 + 9x - 2\)[/tex]
### 1. Adding \(12x^2 + 3x + 6\) and \(-7x^2 - 4x - 2\)
#### Step-by-Step Addition:
- Combine the coefficients of \(x^2\):
\(12x^2 + (-7x^2) = (12 - 7)x^2 = 5x^2\)
- Combine the coefficients of \(x\):
\(3x + (-4x) = (3 - 4)x = -x\)
- Combine the constants:
\(6 + (-2) = 6 - 2 = 4\)
Thus, the sum of the first pair of polynomials is:
[tex]\[5x^2 - x + 4\][/tex]
### 2. Adding \(2x^2 - x\) and \(-x - 2x^2 - 2\)
#### Step-by-Step Addition:
- Combine the coefficients of \(x^2\):
\(2x^2 + (-2x^2) = (2 - 2)x^2 = 0\)
- Combine the coefficients of \(x\):
\(-x + (-x) = (-1 - 1)x = -2x\)
- Combine the constants:
[tex]\[0 - 2 = -2\][/tex]
Thus, the sum of the second pair of polynomials is:
[tex]\[-2x - 2\][/tex]
### 3. Adding \(x^3 + x^2 + 2\) and \(x^2 - 2 - x^3\)
#### Step-by-Step Addition:
- Combine the coefficients of \(x^3\):
\(x^3 + (-x^3) = (1 - 1)x^3 = 0\)
- Combine the coefficients of \(x^2\):
\(x^2 + x^2 = (1 + 1)x^2 = 2x^2\)
- Combine the constants:
\(2 + (-2) = 2 - 2 = 0\)
Thus, the sum of the third pair of polynomials is:
[tex]\[2x^2\][/tex]
### 4. Adding \(x^2 + x\) and \(x^2 + 8x - 2\)
#### Step-by-Step Addition:
- Combine the coefficients of \(x^2\):
\(x^2 + x^2 = (1 + 1)x^2 = 2x^2\)
- Combine the coefficients of \(x\):
\(x + 8x = (1 + 8)x = 9x\)
- Combine the constants:
\(0 + (-2) = -2\)
Thus, the sum of the fourth pair of polynomials is:
[tex]\[2x^2 + 9x - 2\][/tex]
### Final Results:
We have found the sums of the pairs of polynomials as follows:
1. \(5x^2 - x + 4\)
2. \(-2x - 2\)
3. \(2x^2\)
4. [tex]\(2x^2 + 9x - 2\)[/tex]
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.